A new species of acanthoscelides schilsky, 1905 (coleoptera: bruchidae) from Oaxaca, México, with new distribution records of bruchidae for this state - Romero Nápoles, Jesús; Yus-Ramos, Rafael (Instituto de Ecología, A.C., 2008)
A new species of Acanthoscelides collected in Oaxaca, Mexico, is described and figured and new distribution records of Bruchidae for the State are given.